Implementation of UPFC for Voltage Sag Mitigation Using Particle Swarm Optimization - M. Dinesh,; Dr. S. Thangalakshmi, (Journal of Power Electronics and Devices, 2017)
Maintaining the voltage profile in transmission line is very much important to maintain powers system stability. Due to load fluctuations, the voltage in all the buses may not be maintained. FACTS devices are much helpful in voltage compensation. UPFC is one among the FACTS devices which is used to serve this purpose. The load is increased in IEEE 30 bus system to simulate voltage sag condition. The location of UPFC is found using particle swarm optimization (PSO). The power loss during fault and the corresponding dip in voltage is compensated using UPFC. The power flow shows that the voltage in all buses is maintained within the permissible limits. The entire simulation has been demonstrated in IEEE 30 bus system.